Competence of Riau Journalists to Write News in Online Media Using Indonesian Language to Strengthen National Identity - Eka Putra; Muhammad Fithra; Wen Jia; Nuradlin Syafini; Khusnul Hanafi; Harun Mukhtar; W. M. Azim (Jurnal Gramatika, 2024)
Indonesian language has an important role in conveying information clearly to the public and has a significant impact on strengthening national identity. This research is important because it provides insight into the extent to which online media journalists' competence in using Indonesian language can support efforts to strengthen national identity. This research aims to evaluate the competence of online media journalists in Riau in producing news using Indonesian. Researchers used a qualitative approach by conducting in-depth interviews with experienced journalists from various online media in Riau. Data was collected and analyzed to understand the practice of using Indonesian in the entire news writing process, from information search to final writing. The research results show that there is still a lack of optimization of the use of Indonesian language in writing online media news. Journalists tend to use regional languages in data collection in an effort to facilitate the operational stage. Meanwhile, in writing, an informal language style that is in line with everyday language is preferred to attract the attention of readers. These findings illustrate the role of Indonesian language in the context of strengthening national identity and highlight the need to increase the language competence of journalists in Riau.